The Promise of Floating Offshore Wind Power in the Gulf of Maine: New Developments and New Challenges - Shapiro, Jack (Maine Policy Review, 2023)
Maine has set ambitious climate and clean energy goals in the past few years, requiring an economy-wide transition away from fossil fuels. This includes displacing fossil fuel power generation, as well as electrifying end-uses of energy in heating our buildings and fueling our vehicles. This transition will require significant amounts of new renewable energy. This commentary will explore the key role that floating offshore wind will play in in meeting Maine – and New England’s – climate and clean energy goals, including the challenge and promise of being a leader in newer floating offshore wind technology, floating offshore wind technologies being developed at the University of Maine, the role of Maine’s fishing industry, ongoing policy processes like Maine’s Offshore Wind Roadmap, the ongoing federal leasing process in the Gulf of Maine, and the passage of offshore wind procurement legislation during the 2023 legislative session by a broad coalition of environmental and labor organizations.